Driving performance of stable outpatients with depression undergoing real‐world treatment. Issue 6 (30th March 2018) - Miyata, Akemi; Iwamoto, Kunihiro; Kawano, Naoko; Aleksic, Branko; Ando, Masahiko; Ebe, Kazutoshi; Fujita, Kiyoshi; Yokoyama, Motonori; Akiyama, Tsuyoshi; Igarashi, Yoshio; Ozaki, Norio
Abstract : Aim: Although the effects of psychotropics on driving ability have received much attention, little research is available on driving performance of stable outpatients with depression undergoing real‐world treatment. This observational study investigated driving performance, cognitive functions, and depressive symptomatology of partly remitted outpatients with depression under daily‐practice psychopharmacologic treatment. Methods: Seventy stable outpatients with depression and 67 healthy volunteers were enrolled. Patients' prescriptions were not controlled in order to capture the real‐world treatment environment. Participants underwent three driving tasks – road‐tracking, car‐following, and harsh‐braking – using a driving simulator, and three cognitive tasks – Continuous Performance Test, Wisconsin Card Sorting Test, and Trail‐Making Test. The Symptom Assessment Scale – Structured Interview Guide for the Hamilton Depression Rating Scale, Beck Depression Inventory‐II, Social Adaptation Self‐Evaluation Scale, and Stanford Sleepiness Scale were also completed. Results: Although many patients received various pharmacologic treatments, there were no significant differences in the three driving tasks between outpatients with depression and healthy controls. Difficulty of maintaining set in the Wisconsin Card Sorting Test was significantly increased in patients with depression. Results on the Social Adaptation Self‐Evaluation Scale were significantly associated with road‐tracking and car‐following performance, in contrast to results on the Hamilton Depression Rating Scale and the Beck Depression Inventory‐II. Conclusion: We conclude that partly remitted depressive patients under steady‐state pharmacologic treatment do not differ from healthy controls with respect to driving performance, which seems to be more affected by psychosocial functioning than by pharmacologic agents. This, however, should be investigated systematically in an off/on study.